2021
DOI: 10.1021/acs.inorgchem.1c01675
|View full text |Cite
|
Sign up to set email alerts
|

Anthracenyl Functionalization of Half-Sandwich Carbene Complexes: In Vitro Anticancer Activity and Reactions with Biomolecules

Abstract: N-Heterocyclic carbene (NHC) ligands are widely investigated in medicinal inorganic chemistry. Here, we report the preparation and characterization of a series of half-sandwich [M­(L)­(NHC)­Cl2] (M = Ru, Os, Rh, Ir; L = cym/Cp*) complexes with a N-flanking anthracenyl moiety attached to imidazole- and benzimidazole-derived NHC ligands. The anticancer activity of the complexes was investigated in cell culture studies where, in comparison to a Rh derivative with an all-carbon-donor-atom-based ligand (5a), they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…In the case of the Os-Ir compound 2f , minor changes were observed, but these were not as pronounced as those observed for 2c ( Supplementary Figure S22 ). Interestingly, for the Cp* signals in the spectra of both compounds, we observed changes in the aliphatic region which require further investigations ( Banerjee et al, 2018 ; Lee B. Y. T. et al, 2021 ; Lee B. et al, 2021 ). In 10% DMSO- d 6 /D 2 O, the spectra of 2f changed over time which was suppressed by the addition of 100 mM NaCl, to approximate the standard chloride concentration in blood.…”
Section: Resultsmentioning
confidence: 85%
“…In the case of the Os-Ir compound 2f , minor changes were observed, but these were not as pronounced as those observed for 2c ( Supplementary Figure S22 ). Interestingly, for the Cp* signals in the spectra of both compounds, we observed changes in the aliphatic region which require further investigations ( Banerjee et al, 2018 ; Lee B. Y. T. et al, 2021 ; Lee B. et al, 2021 ). In 10% DMSO- d 6 /D 2 O, the spectra of 2f changed over time which was suppressed by the addition of 100 mM NaCl, to approximate the standard chloride concentration in blood.…”
Section: Resultsmentioning
confidence: 85%
“…Other metals from the platinum metal family, in particular, Ir, Os, Rh, and Ru, are employed in the design of novel metal–NHC compounds. We have recently reported a series of [M­(L)­(NHC)­Cl 2 ] complexes (where M = Ru, Os, Rh, Ir; L = η 6 - p -cymene [cym], η 5 -pentamethylcyclopentadienyl [Cp*]) with an N -flanking anthracenyl moiety attached to the NHC ligands, and the complexes showed excellent cytotoxic activity . We have shown that the anthracenyl-functionalized NHC–Ru II (cym) complex forms adducts with hen egg white lysozyme by binding to an Asp residue and a π-stacking interaction with a Trp residue .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a series of [M­(L)­(NHC)­Cl 2 ] complexes (where M = Ru, Os, Rh, Ir; L = η 6 - p -cymene [cym], η 5 -pentamethylcyclopentadienyl [Cp*]) with an N -flanking anthracenyl moiety attached to the NHC ligands, and the complexes showed excellent cytotoxic activity . We have shown that the anthracenyl-functionalized NHC–Ru II (cym) complex forms adducts with hen egg white lysozyme by binding to an Asp residue and a π-stacking interaction with a Trp residue . Interestingly, we showed that [Rh­(Cp*)­(NHC-anthracenyl)­Cl 2 ] A can undergo intramolecular C–C coupling, forming complex B (Figure ) with a seemingly nonadentate all-carbon donor atom ligand. , This involves the activation of the Cp* ligand for reactions at the methyl groups, which also led to intramolecular cross-coupling reactions in Rh­(Cp*)­(NHC) complexes with an N -methylpyridinium- and pentafluorobenzyl-functionalized NHC ligand .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the existing anticancer remedies with metal atoms, Pt-containing compounds (for instance carboplatin, oxaliplatin, and cisplatin) are the most effective and frequently used drugs with long-lasting therapeutic success in the treatment of cancer patients. However, chemotherapy with the Pt-based drugs suffers from many limitations, serious side effects, and, in some cases, lack of selectivity . These barriers and drawbacks have engaged the cancer research field to use other transition metals such as gold, ruthenium, iridium, rhodium, and palladium . Some of these metal complexes, auranofin (Au complex), BOLD-100, and TLD1433 (Ru complexes), progressed to clinical trials and provided an appropriate alternatives for Pt antiproliferative agents.…”
Section: Introductionmentioning
confidence: 99%